PENGAWASAN PUPUK BERSUBSIDI PADA TANAMAN PANGAN OLEH KOMISI PENGAWASAN PUPUK DAN PESTISIDA (KP3) DI KECAMATAN BUNGA RAYA KABUPATEN SIAK - Trimadan, Sandi; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In an effort to implement the subsidized fertilizer program, the Government of Siak Siak issued the decree No. 12 of 2014 About Allocation and top rated retail price Subsidized Fertilizer for Agriculture Sector. Supervision of procurement and distribution of subsidized fertilizer aims to curb the kiosk retailer for the implementation of procurement and distribution does not cause harm and nuisance to farmers subsidized fertilizer users. From observations of researchers in the field largely subsidized fertilizer retailers do not abide by the rules that have been set by the government Siak. The purpose of this study was to determine how the supervision of subsidized fertilizer by the Fertilizer and Pesticide Control Commission Siak and to determine the factors that affect the supervision of subsidized fertilizer in District Bunga Raya.This research was conducted in the District Bunga Raya, using qualitative descriptive method, with the technique of collecting data through observation and interviews. This research was conducted by using the theory according to which Manullang Setting Standards, Conduct Assessment and Corrective Action Hold.Results of this study concluded that the surveillance conducted by the Fertilizer and Pesticide Control Commission Siak against the procurement and provision of subsidized fertilizer at the retail level is not maximized. This is proven by the many kiosk retailers who do not comply with the rules that have been defined in the District Bunga Raya Siak. Factors affecting the supervision consists of internal factors, namely human resources, cost/funding, and infrastructure. External factors derived from subsidized fertilizer retailers who commit violations against predefined rules.Keywords : Control, Subsidized Fertilizer, Procurement and distribution